Pengaruh Penambahan Sukrosa Terhadap Yoghurt Susu Kacang Tolo Menggunakan Kultur Campuran Bakteri Asam Laktat Sebagai Makanan Pokok - Indhira Shagti (JURNAL INFO KESEHATAN, 2017)
Tolo bean milk yogurt is a functional food derived from vegetable milk made from beans Tolo that contains protein, lysine, aspartic acid and glutamic acid are relatively high, so good for vegetarians and people with lactose intolerance, and can improve intestinal microflora. Yogurt is a functional food containing lactic acid bacteria which can reduce cholesterol levels and increase endurance. Have believed that functional foods can prevent or decrease the likelihood of disease. This study aimed to analyze the quality of microbiological and chemical quality of yogurt peanut Tolo seen from the influence of sucrose. This study is a pure experiment, with variable effect is the addition of sucrose (4%, 6%, 8% and 10%). Variable quality affected are chemical (pH, total acid) and microbiological quality (total lactic acid bacteria). Analysis of the data is tabulated and presented in a descriptive narrative. Values of pH, total acid levels, and BAL are affected by the treatment, Treatment P3 and P4 by the addition of sucrose 8% and 10% had the lowest pH value of 3.3 and a total acid content of the highest 1% and has a total of lactic acid bacteria highest.